Case Report: Drug-induced liver injury mimicking hypereosinophilic syndrome - Yapali, Suna; Yucel, Serap; Sariguzel, Nevin; Saruç, Murat; Unal, Hakan Umit; Tiftikci, Arzu; Kutsal, Eser; Onder, Oguz Fatih; Sisman, Gurhan; Aygun, Cem; Ersoy, Ozdal; Kiziltas, Safak; et al. (Turkish Journal of Gastroenterology, 2019)
A 56 year-old male presented with cough starting 3 months ago and jaundice and fatigue for one week. Labs showed ALT: 1994 IU/mL, AST: 1331 IU/mL, ALP: 221 U/L, GGT: 182 U/L, T.Bilirubin: 10.1 mg/dL, D.Bilirubin: 7.4 mg/dL, Prothrombin Time/INR: 31.8 sec/2.38, WBC: 28.900/mm3 and Eosinophil count: 14,450. ESR: 68/hr. He had a travel history to Phuket, New York, Israel and Germany in the past 3 months, and reported walking in the sewage with open toe slippers at Phuket. Normal physical exam except for jaundice. Thorax CT done a week ago revealed 1.5 cm nodular lesion and ≈1 cm mediastinal LAP and FDG uptake of the lung nodule, spleen and bone marrow on the PET scan. He consumed 10 boxes of bronchomax syrup (extracts of combination of herbals), Umca syrup (pelargonium sidoides), vardenaphile, glucasamine, milk thistle and 250 mg of powder curcumin to stop his cough in the past 3 months. The presentation with acute hepatitis, leukocytosis, eosinophilia, high ESR and high FDG uptake on the PET scan prompted the differential diagnosis of acute viral hepatitis, autoimmune hepatitis, parasitic infection, hypereosinophilic syndrome, myeloproliferative Diseases/Lymphoma, sarcoidosis, solid malignancy and DILI. Serology for viral hepatitis including HAV, HBC, HCV (and HCV RNA), HIV, HEV, EBV, CMV and HSV was negative. Protein electrophoresis and autoantibodies were negative. Abdominal imaging was normal. IgE: 435 (NCONCLUSION: The liver injury was probably due to an idiosyncratic hypersensitivity reaction by the combination of herbal supplements, which also triggered an antigenic stimulation of bone marrow resulting hypereosinophilia.